2023
DOI: 10.1002/cpp.2821
|View full text |Cite
|
Sign up to set email alerts
|

Anger profiles among individuals seeking treatment for maladaptive anger: Associations with emotion regulation

Abstract: Individuals who experience problems with anger represent a heterogeneous group. Identifying clinically relevant subtypes of anger may advance treatment research. In the current study, latent profile analysis (LPA) was conducted to explore if distinct subtypes of anger could be identified within a sample of individuals seeking treatment for maladaptive anger (N = 538; 55.4% females; mean age = 39.78, SD = 12.28). Furthermore, the utility of the empirical classification was examined based on differences in usage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Manuscript 1 (the present article) focuses on STAXI-2, AQ, and ARS reported at baseline, during treatment, posttreatment, and at 3-month follow-up. Manuscript 2 (Larsson et al, 2022) focuses on STAXI-2, AQ, and ARS reported at baseline. While there is some overlap in variables, the research questions, analyzed sample, and analytical procedure are different from Manuscript 1.…”
Section: Data Transparencymentioning
confidence: 99%
“…Manuscript 1 (the present article) focuses on STAXI-2, AQ, and ARS reported at baseline, during treatment, posttreatment, and at 3-month follow-up. Manuscript 2 (Larsson et al, 2022) focuses on STAXI-2, AQ, and ARS reported at baseline. While there is some overlap in variables, the research questions, analyzed sample, and analytical procedure are different from Manuscript 1.…”
Section: Data Transparencymentioning
confidence: 99%
“…Another strategy commonly involved in overregulation of anger is rumination (Larsson et al, 2023). Anger rumination refers to a cognitive‐emotional process of dwelling on past anger experiences and frustrations (Sukhodolsky et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In essence, ruminative anger may function as a secondary emotion in warding off unwanted primary emotions (for a more in‐depth exploration of anger as a primary and secondary emotion; see Pascual‐Leone et al, 2013). Although distinct, under‐ and overregulation can also coexist (Furlong & Smith, 1998; Larsson et al, 2023). For instance, an individual may have problems inhibiting angry behavior and aggressive impulses in certain situations whilst continuously suppressing and avoiding anger in others.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations